SCHOLARS IN THE MAKING: UNRAVELLING THE PUBLICATION QUEST THROUGH A COMMUNITY OF WRITING PRACTICE - Rahmah Fithriani; Benni Ichsanda Rahman Hz; Eka Yuni Kurniati (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTAlthough many studies have been conducted to investigate how graduate students navigate the publication endeavor as a graduation requirement, a scant number have explicitly focused on how Master's students manage to do so through their participation in a community of practice (CoP). This study set out to bridge this gap by examining the transformation experienced by Indonesian Master's students of English education in terms of their knowledge and practice in writing for scholarly publication after joining a writing group. This study employed a qualitative, descriptive case study approach. Data were collected through a questionnaire, in-depth interviews, and artifact analysis from 15 students and analyzed using Content Analysis. Findings indicate that after joining the writing group, the students reported increased skills in writing scholarly articles and more knowledge of the publication process. This study suggests the establishment of communities of writing practice in graduate programs to assist students in addressing the mounting pressure of scholarly publication, either as degree conferment or career preparation and advancement. ABSTRAKMeskipun segudang penelitian telah dilakukan untuk menyelidiki bagaimana mahasiswa pascasarjana menavigasi upaya publikasi sebagai syarat kelulusan, hanya sedikit penelitian yang berfokus secara khusu pada bagaimana mahasiswa magister berhasil melakukannya melalui keikutsertaan mereka dalam komunitas praktik (CoP). Penelitian ini bertujuan untuk menjembatani kesenjangan tersebut dengan mengkaji transformasi yang dialami oleh mahasiswa magister pendidikan bahasa Inggris di Indonesia terkait pengetahuan dan praktik menulis untuk publikasi ilmiah setelah bergabung dengan kelompok menulis. Penelitian ini menggunakan pendekatan kualitatif deskriptif studi kasus. Data dikumpulkan melalui angket, wawancara mendalam, dan analisis artefak dari 15 mahasiswa dan dianalisis dengan Content Analysis. Temuan menunjukkan bahwa setelah bergabung dengan kelompok menulis, para mahasiswa melaporkan peningkatan keterampilan dalam menulis artikel ilmiah dan pengetahuan yang lebih baik tentang proses publikasi. Studi ini menyarankan pembentukan komunitas praktik menulis dalam program pascasarjana untuk membantu mahasiswa mengatasi tekanan berat dalam publikasi ilmiah, baik sebagai persyaratan untuk mendapatkan gelar atau persiapan dan kemajuan karir.How to Cite: Fithriani, R., Rahman Hz, B.I., Kurniati, E.Y. (2023). Scholars in the Making: Unravelling the Publication Quest Through a Community of Writing Practice. IJEE (Indonesian Journal of English Education), 10(1), 221-238. doi:10.15408/ijee.v10i1.31457.